Sol–Gel Synthesis and Formation Mechanism of Ultrahigh Temperature Ceramic: HfB2. Issue 1 (28th November 2013) - Venugopal, Saranya; Boakye, Emmanuel E.; Paul, Anish; Keller, Kristin; Mogilevsky, Pavel; Vaidhyanathan, Bala; Binner, Jon G. P.; Katz, Allan; Brown, Peter M.
Abstract : Hafnium diboride (HfB2 ) powder has been synthesized via a sol–gel‐based route using phenolic resin, hafnium chloride, and boric acid as the source of carbon, hafnium, and boron, respectively, though a small number of comparative experiments involved amorphous boron as boron source. The effects of heat‐treatment dwell time and hafnium:carbon (Hf:C) and hafnium:boron (Hf:B) molar ratio on the purity and morphology of the final powder have been studied and the mechanism of HfB2 formation investigated using several techniques. The results showed that while temperatures as low as 1300°C could be used to produce HfB2 particles, the heat treatment needed to last for about 25 h. This in turn resulted in anisotropic particle growth along the c ‐axis of the HfB2 crystals yielding tube‐like structures of about 10 μm long. Equiaxed particles 1–2 μm in size were obtained when the precursor was heat treated at 1600°C for 2 h. The reaction mechanism involved boro/carbothermal reduction and the indications were that the formation of HfB2 at 1300°C is through the intermediate formation of an amorphous B or boron suboxides, although at higher temperatures more than one reaction mechanism may be active.